Monotonicity of Product of Functions

Calculus Level 3

A function f ( n ) f(n) is monotonically increasing on some interval [ a , b ] [a,b] if for every m , n [ a , b ] m, n \in [a,b] , m n m \leq n implies f ( m ) f ( n ) f(m) \leq f(n) .

Is the following statement TRUE ?

If f ( n ) f(n) and g ( n ) g(n) are monotonically increasing functions on [ a , b ] [a,b] , then f g ( n ) fg(n) is also monotonically increasing on [ a , b ] [a,b] .

Notations:

  • [ a , b ] = { x R : a x b } [a,b] = \{ x \in \mathbb{R} : a \leq x \leq b\} , where a , b R a, b \in \mathbb{R} with a b a\leq b .

  • f g ( n ) = f ( n ) × g ( n ) fg(n) = f(n) \times g(n) , for every n n belonging to the intersection of the domains of f ( n ) f(n) and g ( n ) g(n) .

No Yes

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Consider f ( n ) = n 4 f(n)=n-4 and g ( n ) = n 2 g(n)=n-2 who are monotonically increasing on [ 0 , 100 ] [0,100] .

But " 1 3 f g ( 1 ) f g ( 3 ) 1 \leq 3 \implies fg(1) \leq fg(3) " is false, hence, the statement is F A L S E FALSE .

f g ( 1 ) = f ( 1 ) × g ( 1 ) = 3 > f g ( 3 ) = f ( 3 ) × g ( 3 ) = 1 fg(1)= f(1) \times g(1)=3 > fg(3)=f(3) \times g(3)= -1 .

By the way, you can verify this fact:

If f ( n ) f(n) and g ( n ) g(n) are monotonically increasing functions on [ a , b ] [a,b] AND each of f ( n ) f(n) and g ( n ) g(n) possibly touches the x a x i s x-axis but doesn't cut it over the interval [ a , b ] [a,b] , then f g ( n ) fg(n) is also monotonically increasing on [ a , b ] [a,b] .

Yes, for a function f ( n ) f(n) , " f ( n ) f(n) possibly touches the x a x i s x-axis but doesn't cut it over the interval [ a , b ] [a,b] " is equivalent to to saying exactly one of the following:

  • f ( n ) 0 f(n) \geq 0 for every n [ a , b ] n \in [a,b] . (All the way Non-negative )

  • f ( n ) 0 f(n) \leq 0 for every n [ a , b ] n \in [a,b] . (All the way Non-positive )

Sign change should not be there

Kushal Bose - 4 years, 6 months ago

Log in to reply

Yeah. It's so.

Muhammad Rasel Parvej - 4 years, 6 months ago

The trivial example is f ( n ) = g ( n ) = n f(n) = g(n) = n . However, your answer seems correct.

Michael Huang - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...